1997
DOI: 10.1002/elps.1150181536
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of the diastereomers of a large synthetic peptide by capillary electrophoresis using nonionic surfactants

Abstract: A capillary electrophoretic method was developed for the determination of the diastereomeric composition of the bradykinin B2 antagonist, SB-238592-DB. The nonionic surfactant Brij 35 was demonstrated to be suitable for the baseline resolution of the three diastereoisomers of SB-238592-DB in the presence of a low pH phosphate buffer and small volume percentages of acetonitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The separation of neutral analytes by MEKC in zwitterionic surfactant-based media (Rewoteric AM CAS U, Zwittergen 4-14 and polyalkylammonium propanesulfonate analogues) bears no difficulty since these chemicals can own net charge depending on the conditions. Since their introduction to modify the selectivity of electrokinetic separations [42][43][44][45][46][60][61][62][63], the employment of both nonionic and zwitterionic surfactants has become a common practice for the analysis of proteins and peptides [51][52][53][54][55][56][57][58][59][64][65][66][67][68], stereoisomers [64,67,68] and other closely related compounds [69][70][71][72][73][74].…”
Section: Nonconventional Pseudostationary Phases 31 Nonionic and Zwimentioning
confidence: 99%
“…The separation of neutral analytes by MEKC in zwitterionic surfactant-based media (Rewoteric AM CAS U, Zwittergen 4-14 and polyalkylammonium propanesulfonate analogues) bears no difficulty since these chemicals can own net charge depending on the conditions. Since their introduction to modify the selectivity of electrokinetic separations [42][43][44][45][46][60][61][62][63], the employment of both nonionic and zwitterionic surfactants has become a common practice for the analysis of proteins and peptides [51][52][53][54][55][56][57][58][59][64][65][66][67][68], stereoisomers [64,67,68] and other closely related compounds [69][70][71][72][73][74].…”
Section: Nonconventional Pseudostationary Phases 31 Nonionic and Zwimentioning
confidence: 99%
“…2003, 26, 653-660 As an example of diastereomer separation of peptides in achiral conditions, a paper of Zhang et al [14] dealing with 13 pairs of diastereomers of synthetic L-Ala and D-Ala analogs of a tridecapeptidic pheromone by CZE in phosphate BGEs can be cited. Gilges et al [15] reported a separation of diastereomers of a bradykinin B 2 antagonist by MEKC with non-ionic surfactants and Hansen et al [16] separated dipeptide diastereomers by nonaqueous capillary electrophoresis.…”
Section: Introductionmentioning
confidence: 98%
“…The separation characteristics ofa micellar phase can, therefore, also be manipulated by changing the surfactant. Several types of surfactant have been employed in MEKC, including anionic surfactants such as SDS [10][11][12][13], cationic surfactants such as CTAB [7,[12][13][14], non-ionic surfactants such as the Brij or the Tween series of surfactants [15][16][17][18] and zwitterionic surfactants [17]. The micellar phase can also be modified by adding a second surfacrant to form a mixed micellar system [5,8,11,19], or by selecting a different counterion [20].…”
Section: Introductionmentioning
confidence: 99%